Child disability and caregiving in low and middle income countries: Big data approach on open data. (December 2020) - Bizzego, Andrea; Lim, Mengyu; Schiavon, Greta; Setoh, Peipei; Gabrieli, Giulio; Dimitriou, Dagmara; Esposito, Gianluca
Highlights: Data-driven analysis of child disability revealed systematic differences in caregiving. Children with intellectual disability at higher risk of caregiving neglect. Neglect moderated by gender, education level and human development index. Abstract: Background: The presence of child disabilities might affect the amount of caregiving attention the child receives, with potential ramifications on the development of the child and increasing the likelihood of developing a more severe condition. Little is known about the association between child disabilities and caregiving practices in less developed countries, penalized by both lack of data and a research bias toward western societies. Method: In this study, we apply data mining methods on a large ( N = 29, 525) dataset from UNICEF to investigate the association between caregiving practices and developmental disabilities of the children, and highlight the differences between intellectual and other disabilities. Results: Our results highlight that, compared to other types of disabilities, intellectual disabilities increased the risk of being neglected by the caregiver in those activities oriented to the cognitive development. The education of the caregiver and the socioeconomical development of the country are actively involved in the moderation of the risk. Conclusion: We demonstrated that educational policies of parental training, such as psychoeducation regarding intellectual disabilities and destigmatization campaigns, are needed to benefit parental practices in low- and middle-income countries.